2013
DOI: 10.1016/j.jiph.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV infection among tuberculosis patients in Eastern India

Abstract: The prevalence of HIV-TB co-infection was 12.3%. Consequently, all TB patients should be assessed for HIV risk factors and counseled to undergo HIV testing. Conversely, all HIV-positive cases should be screened for TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
39
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 7 publications
12
39
6
Order By: Relevance
“…Similarly, the co-infection risk was higher for the same age bracket, which implied that co-infection was more common in the sexually active age group. These findings were contrary to the findings by (32) and (29) who observed that high rates of TB-HIV co-infections were in younger patients (<15 years of age) but consistent to several other studies (30,(33)(34)(35)(36). The study also revealed that a larger proportion of the HIV co-infected cases had extra-pulmonary TB conforming to (37) and (34) who found that the risk of extrapulmonary TB was higher in HIV co-infected cases majorly because of delayed diagnosis especially for the sputum smear-negative…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, the co-infection risk was higher for the same age bracket, which implied that co-infection was more common in the sexually active age group. These findings were contrary to the findings by (32) and (29) who observed that high rates of TB-HIV co-infections were in younger patients (<15 years of age) but consistent to several other studies (30,(33)(34)(35)(36). The study also revealed that a larger proportion of the HIV co-infected cases had extra-pulmonary TB conforming to (37) and (34) who found that the risk of extrapulmonary TB was higher in HIV co-infected cases majorly because of delayed diagnosis especially for the sputum smear-negative…”
Section: Discussionsupporting
confidence: 72%
“…The larger TB case notification among the male could be because of the barriers the female encounter in seeking care for and diagnosis of TB or could reflect more complete registration for treatment by the male (42). In other studies by (34), the prevalence of co-infection was much higher among males in most countries in Sub-Saharan Africa whereas in all other countries there was no significant difference in the gender ratio. However, the case notification data alone are insufficient to determine whether the gender ratio reflect an excess in the co-infection burden among men or a disadvantage among women in seeking and accessing TB care.…”
Section: Discussionmentioning
confidence: 82%
“…With these WHO declared TB as global public health emergency. One of the reports mentioned that out of the 9 million reported TB cases, 2 million were from Indian subcontinent [13].…”
Section: Discussionmentioning
confidence: 99%
“…13 In a study among patients in a railway hospital in Kolkata coughing and fever were the common presentation. 14 In pediatric age group also predominant symptoms were cough, fever, loss of weight and loss of appetite. 8 Problem of tuberculosis has been compounded by the presence of different co morbidities.…”
Section: Discussionmentioning
confidence: 99%